Соло трех дам: лирические фантазии / Н. П. Иевлев - Иевлев Николай Павлович (Удмуртия, 2005)
Экземпляры: ЦБ (20080821) / Инвентарный номер: 40229 / Цена: 50.00 / Авт.знак: И 30 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)